Metode Menentukan Mitra Bisnis Pada â€œKomunitas Tanpa Ribaâ€ Di Malang - khusnudin us din (ITB AAS INDONESIA Surakarta, 2023)
Business activities will be more accessible if done with partners. Determining the right business partner is the main factor in achieving the business's success. The interrelation of the parties in running the business to gain profits will be easier with suitable partners. Various methods are used to determine the right business partner. The determining factors of a business partner's feasibility that satisfy the needs of a non-profit community is an interesting research topic. Qualitative research was conducted using a phenomenological approach with